Dosimetric Impact of Inter-Fraction Variability in the Treatment of Breast Cancer: Towards New Criteria to Evaluate the Appropriateness of Online Adaptive Radiotherapy - Iezzi, Martina; Cusumano, Davide; Piccari, Danila; Menna, Sebastiano; Catucci, Francesco; D’Aviero, Andrea; Re, Alessia; Di Dio, Carmela; Quaranta, Flaviovincenzo; Boschetti, Althea; Marras, Marco; Piro, Domenico; et al. (Frontiers in Oncology, 2022)
As a discipline in its infancy, online adaptive RT (ART) needs new ontologies and ad hoc criteria to evaluate the appropriateness of its use in clinical practice. In this experience we propose a predictive model able to quantify the dosimetric impact due to daily inter-fraction variability in a standard RT breast treatment, to early identify the treatment fractions where patients might benefit of an online ART approach. The study was focused on right breast patients treated using standard adjuvant RT on an Artificial Intelligence (AI)-based accelerator. Patients were treated with daily CBCT images and without online adaptation, prescribing 40.05Gy in 15 fractions, with four IMRT tangential beams. ESTRO guidelines were followed for the delineation on planning CT(pCT) of organs at risk and targets. For each patient, all the CBCT images were rigidly aligned to pCT: CTV and PTV were manually re-contoured and the original treatment plan was recalculated. Various radiological parameters were measured on CBCT images, to quantify inter-fraction variability present in each RT fraction after couch shifts compensation. The variation of these parameters was correlated with the variation of V95% of PTV (ΔV95%) using the Wilcoxon Mann Whitney test. Fractions where ΔV95%>2% were considered as adverse events. A logistic regression model was calculated considering the most significant parameter and its performance were quantified with Receiver Operating Characteristic (ROC) curve. A total of 75 fractions on 5 patients were analysed. The body variation between daily CBCT and pCT along the beam axis with highest MU was identified as best predictor (p=0.002). The predictive model showed an area under ROC curve of 0.86 (0.82-0.99 as 95%CI) with sensitivity of 85.7% and specificity of 83.8% at the best threshold which was equal to 3 mm. A novel strategy to identify treatment fractions which may benefit of online ART was proposed. After image alignment, the measure of body difference between daily CBCT and pCT can be considered as an indirect estimator of V95% PTV variation: a difference larger than 3mm will results in a V95% decrease larger than 2%.A larger number of observations is needed to confirm the results of this hypothesis-generating study